ON CAMPUS IOT DEMONSTRATION FOR STUDENT HOTSPOT TRACKING USING WIRELESS SENSORS NETWORK AND INTEGRATED SOFTWARE PLATEFORM - SUKRI, FIRMAN SYAH (2017)
Internet of Things(IoT) has become a new trend for technology development. The current communication technology that making wireless technology becoming more reliable is one of the factor that promote IoT ideas. IoT offer a more effective solution to record, manage, process and sharing of information via internet. This technology is will associate with a sensor that always take a new data and directly send the data to the server via Wi-Fi. Bluetooth technology are now promoting Low Energy (LE) device that has a longer range and lower power consumption. Bluetooth can be used as a measuring instrument to measure the Received Signal Strength Indication(RSSI) from other Bluetooth device. The RSSI value can be used to derived a distance between the transmitter and receiver of that communication. Based on this approximate distance value from RSSI, this project will implement triangulation algorithm to estimate the location of a receiver based on the 3 estimated that send by the three known receiver.